Hustlers [videorecording (DVD)] - Scafaria, Lorene; Scafaria, Lorene; Wu, Constance, 1982-; Lopez, Jennifer, 1970-; Lopez, Jennifer, 1970-; Stiles, Julia, 1981-; Pressler, Jessica (Universal Pictures Home Entertainment, 2019)
A crew of savvy former employees at a New York City strip club band together to turn the tables on their Wall Street clients.